Hyperventilation-Induced Nystagmus in Acute Unilateral Vestibulopathy: A Correlation with Vestibulo-ocular Reflex Gain and Clinical Implication - Giacomo Ciacca; Alfredo Di Giovanni; Giacomo Lupinelli; Mario Gullà; Giampietro Ricci; Mario Faralli (Journal of International Advanced Otology)
BACKGROUND: Hyperventilation-induced nystagmus test (HINT) is capable of generating a response in 77.2% of cases of acute unilateral vestibulopathy (AUVP); both nystagmus toward the affected side (excitatory pattern) and toward the healthy side (inhibitory pattern) have been described. The aim of the study is to investigate the clinical and prognostic role of the test by evaluating its correlation with vestibulo-ocular reflex (VOR) gain.